2020
DOI: 10.1073/pnas.2008456117
|View full text |Cite
|
Sign up to set email alerts
|

Targeting presynaptic H3 heteroreceptor in nucleus accumbens to improve anxiety and obsessive-compulsive-like behaviors

Abstract: Anxiety commonly co‐occurs with obsessive-compulsive disorder (OCD). Both of them are closely related to stress. However, the shared neurobiological substrates and therapeutic targets remain unclear. Here we report an amelioration of both anxiety and OCD via the histamine presynaptic H3 heteroreceptor on glutamatergic afferent terminals from the prelimbic prefrontal cortex (PrL) to the nucleus accumbens (NAc) core, a vital node in the limbic loop. The NAc core receives direct hypothalamic histaminergic project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…In this context, it has been recently reported that stress‐evoked HA signalling recruits a presynaptic gain control mechanism at glutamatergic synapses in the NAc, an effect that is mediated by H3R (Manz et al., 2021). Moreover, it has been demonstrated that activation of the histaminergic afferent system, particularly the histamine H3R, inhibits glutamatergic synaptic transmission in the circuit from the prelimbic prefrontal cortex to the NAc and improves both anxiety‐ and obsessive‐compulsive‐like behaviours induced by restraint stress (Zhang et al., 2020). The H2R‐dependent enhancement of MSN excitability we observed in this study could conceivably represent another mechanism by which elevated extracellular histamine levels, following acute stress, may induce stress‐dependent decisional strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been recently reported that stress‐evoked HA signalling recruits a presynaptic gain control mechanism at glutamatergic synapses in the NAc, an effect that is mediated by H3R (Manz et al., 2021). Moreover, it has been demonstrated that activation of the histaminergic afferent system, particularly the histamine H3R, inhibits glutamatergic synaptic transmission in the circuit from the prelimbic prefrontal cortex to the NAc and improves both anxiety‐ and obsessive‐compulsive‐like behaviours induced by restraint stress (Zhang et al., 2020). The H2R‐dependent enhancement of MSN excitability we observed in this study could conceivably represent another mechanism by which elevated extracellular histamine levels, following acute stress, may induce stress‐dependent decisional strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a quinpirole (QNP)-induced OCD rat model was adopted, and the open field test (OFT) relevant to compulsive checking behavior and the elevated plus maze (EPM) were used for the behavioral assessment (Szechtman et al, 1998(Szechtman et al, , 2017Hoffman, 2011). Given that the core of the NAc mediates the control of goal-oriented behaviors and obsessive-compulsive-like behaviors (Di Chiara, 2002;Zhang et al, 2020), micro-electrodes were implanted into the NAc core for stimulation and recording. Then SPK signals were recorded to obtain information about neuronal firing patterns, including the firing rate and indicators of interspike interval (ISI), including the coefficient of variance (CV) and asymmetry index (AI) (Alam et al, 2012(Alam et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that as parts of the brain reward system, the right and left NAcc function reflects how individuals respond to cues that signal a potential reward [1]. The right and left NAcc have also been implicated in obesity [2,6], food addiction [7], tobacco, alcohol, and drug-seeking behaviors [8][9][10], obsessive-compulsive disorder [11,12], depression [13], and anxiety [12].…”
Section: Introductionmentioning
confidence: 99%